1982
DOI: 10.1104/pp.69.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Nitrate Influx and Reduction in Corn Seedlings Exposed to Ammonium

Abstract: The effect of ambient ammonium (0.5 (10,23,24,25,28,31). In contrast, either no effect or an enhancement of NRA in the presence of ammonium has been reported (3,23,24,31).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
2

Year Published

1983
1983
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 25 publications
5
27
2
Order By: Relevance
“…There have also been reports of stimulated NO3-uptake arising as a consequence of NH4' pretreatment as in the case of seedlings of wheat (21) and corn (18).…”
Section: Introductionmentioning
confidence: 99%
“…There have also been reports of stimulated NO3-uptake arising as a consequence of NH4' pretreatment as in the case of seedlings of wheat (21) and corn (18).…”
Section: Introductionmentioning
confidence: 99%
“…Also, ⌽* xylem in NO 2 Ϫ -induced plants was substantially lower than in NO 3 Ϫ -induced plants, and approximated that of plants induced at 0.1 mm [NO 3 Ϫ ] o after the application of 1 mm NH 4 ϩ . Because significant suppression of NO 3 Ϫ reductase activity by NH 4 ϩ is well documented (MacKown et al, 1982a(MacKown et al, , 1982bBreteler and Siegerist, 1984;Pan et al, 1985;de la Haba et al, 1990;Aslam et al, 1997;however, see Oaks et al, 1979), ⌽* xylem under these conditions will be mostly in the form of 13 NO 3 Ϫ after NH 4 ϩ addition. Therefore, the lack of an effect of NH 4 ϩ on Figure 2.…”
Section: N-flux Partitioningmentioning
confidence: 99%
“…Although early reports suggested that NH 4 ϩ enhanced NO 3 Ϫ efflux (Jackson et al, 1976;Doddema and Telkamp, 1979;MacKown et al, 1982a;Deane-Drummond and Glass, 1983;Deane-Drummond, 1985, 1986, later studies using 13 NO 3 Ϫ clearly documented an inhibition of influx (Glass et al, 1985;Lee and Clarkson, 1986;Ingemarsson et al, 1987;Oscarson et al, 1987;Lee and Drew, 1989;Ayling, 1993;King et al, 1993). The debate has recently been revived by Aslam andcoworkers (1994, 1997), who concluded that the main effect of NH 4 ϩ on net NO 3 Ϫ uptake was through stimulation of NO 3 Ϫ efflux; they discounted the significance of influx inhibition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By using 36C103-as an analog for NO3-, it was shown that NH4+ stimulated NO3-efflux in several species (4)(5)(6)(7), although no such effect was found in barley using '3N03- (17). Studies with '5NO3- (18) and '3N03- (11,22) rather pointed to an inhibition of the influx component of net NO3-uptake. There is only limited knowledge on the cause for inhibition of NO3-uptake; it has been attributed to NH4+-induced membrane depolarization (27), or to a regulatory compound formed in primary NH4' assimilation (1,10).…”
mentioning
confidence: 96%